The Paper that Restarted Modern Central Nervous System Axon Regeneration Research - Fawcett, James W (Trends in neurosciences, 2018)
Spinal cord repair research appeared to have run out of new ideas in the 1970s. In a 1981 paper, the Aguayo Laboratory revisited an experiment by Tello and Cajal that suggested that central nervous system (CNS) axons could regenerate into peripheral nerve grafts. Using modern axon tracing methods, David and Aguayo showed that axons from neurons in the spinal cord could regenerate for long distances within peripheral nervous system (PNS) grafts, but not back into the CNS. This proved that damaged CNS tissue is inhibitory to axon regeneration while PNS tissue is permissive. The experiment sparked a research revival, leading to the identification of many inhibitory molecules that block axon growth in the mature CNS.
Keywords: Peripheral Nervous System; krysa rodu Rattus; Animals; regenerace nervu; Central Nervous System; Nerve Regeneration; Spinal Cord Injuries; spinal cord injury; zvířata; centrální nervový systém; periferní nervový systém; axony; poranění míchy; Trauma, Nervous System; Rats; poranění nervového systému; axon regeneration; Axons